2018
DOI: 10.1111/1365-2435.13234
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interactions shape the adaptive value of plant defence: Herbivore attack versus competition for light

Abstract: Plants defend themselves against diverse communities of herbivorous insects. This requires an investment of limited resources, for which plants also compete with neighbours. The consequences of an investment in defence are determined by the metabolic costs of defence as well as indirect or ecological costs through interactions with other organisms. These ecological costs have a potentially strong impact on the evolution of defensive traits, but have proven to be difficult to quantify. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…For annual plants, the main defence strategy early in plant development is resistance, while later in plant development this switches to tolerance (Boege et al, ). Increased investment of black mustard in resistance and loss of important photosynthetic tissues due to herbivore damage early in life will be especially expensive (de Vries et al, , ). This can explain our observed reduction in flowers, the number of seeds produced and seed weight for plants exposed in the vegetative stage to P. brassicae caterpillars or B. brassicae aphids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For annual plants, the main defence strategy early in plant development is resistance, while later in plant development this switches to tolerance (Boege et al, ). Increased investment of black mustard in resistance and loss of important photosynthetic tissues due to herbivore damage early in life will be especially expensive (de Vries et al, , ). This can explain our observed reduction in flowers, the number of seeds produced and seed weight for plants exposed in the vegetative stage to P. brassicae caterpillars or B. brassicae aphids.…”
Section: Discussionmentioning
confidence: 99%
“…Second, investment in one component may alter plant interactions with other community members (de Vries, Evers, & Poelman, ; Dutton, Luo, Cembrowski, Shore, & Frederickson, ; Lucas‐Barbosa, ; Villamil, ). For example, large plants may be more apparent to herbivores as a result of increased investment in growth induced by competition for light (de Vries, Evers, Dicke, & Poelman, ). Plant defence responses to herbivory can affect plant reproduction by changes in flowering time, flower abundance and plant interactions with flower visitors (Rusman, Lucas‐Barbosa, Poelman, & Dicke, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the advantage of a defence gradient is expected to become even stronger when insect herbivores prefer to feed on young leaves near the tip of the branches. Second, the gradient in leaf defence expression within a canopy as established by R:FR can benefit the plant by dispersing herbivore damage away from young leaves (Cipollini et al, ), which is shown to benefit plants in competition with conspecifics, but only under high herbivore pressure (de Vries, Evers, Dicke, & Poelman, ; de Vries, Poelman, et al, ). If this effect would have been included in this study, it would have resulted in a bigger advantage of R:FR‐mediated defence.…”
Section: Discussionmentioning
confidence: 99%
“…allowing information sharing and communication between them [193]. This sharing may be favorable despite the cost of alarm signaling toward potential competitor species [194]. Indeed, it allows cooperation in herbivore insect exclusion from their common neighborhood through herbivoreinduced plant volatile molecules acting via epigenetic mechanisms that sustain the memorization of the defense response [195].…”
Section: Cell Communications Between Plantsmentioning
confidence: 99%